Effects of linear and change of direction high-intensity interval training on physical performance of elite female soccer players - Stanković, Mima; Trajković, Nebojša; Mačak, Draženka; Đorđević, Dušan; Lazić, Anja; Milanović, Zoran (Biology of Sport, 2024)
The aim of this study was to determine the effects of linear and change of direction high intensity interval training (HIIT) on physical performance in elite female soccer players. Thirty elite female soccer players (age: 19.6±4.6 years; height: 166.5±4.8 cm; body weight: 60.5±8.3 kg; BMI: 21.9±2.9 kg/m 2 ) were randomly allocated to HIIT linear (HIIT LIN ) and HIIT change of direction (HIIT COD ) training groups. The HIIT LIN group performed linear running for 15, 20 or 25 s by keeping constant pace during the entire distance. In contrast, the HIIT COD group performed three changes of direction (COD) with a 180° turn during each interval run at 15, 20 or 25 s. Physical performance was assessed using sprinting, agility, vertical jumps, repeated sprint ability (RSA) and 30–15 Intermittent Fitness Test (30–15 IFT). In both groups, all physical performance measurements improved ( p ≤ 0.05), except RSAbest in HIIT LIN ( p = 0.45). Both interventions significantly improved speed over 10 m, 20 m, 30 m, Pro agility, Zig-zag, RSAavg, fatigue index, maximal oxygen uptake, and velocity at 30–15 IFT, while moderate improvements were observed in countermovement jump (CMJ), CMJ with arm swing and squat jump. However, HIIT COD did not achieve superior improvements in any of the aforementioned measurements compared to HIIT LIN . Based on the obtained results, we concluded that different types of HIIT training have a positive effect on physical performance in elite female soccer players.